Esophageal diameter as a function of weight in neonates, children and adolescents: reference values for dilatation of esophageal stenoses - Loff, Steffan; Diez, Oliver; Ho, Wei; Kalle, Thekla v; Hetjens, Svetlana; Boettcher, Michael (Frontiers in Pediatrics, 2022)
Introduction: Esophageal stenoses are frequent complications after esophageal atresia surgery as well as after acid, alkali and battery ingestion. Worldwide, repeated balloon dilatations are the most frequently performed procedures for these stenoses. In most cases the stenoses can be dilated sufficiently to allow adequate enteral nutrition. Until recently, age dependent esophageal lumen size has not been established; which was aim of the current study. Methods: All children in whom an esophageal contrast x-ray was performed between 1/2011 and 5/2021 were included. The width was measured by two investigators at two measuring points in two planes and plotted against the respective weight of the child. Bland-Altmann plots have confirmed the validity of the measurements of both investigators. Results: Esophagus width was measured in more than 100 children. The resulting curves show a very good correlation with weight (upper measuring point: r= 0.86743, p<0.0001; lower measuring point: r= 0.80593, p<0.0001). Conclusion: Our results are the first to define the esophageal width in children. The results of our study may guide physicians performing esophageal interventions including dilatations in future.